Pengaruh Penggunaan Media Sosial Terhadap Hasil Belajar Siswa Kelas XI IPS Pada Mata Pelajaran Ekonomi Di SMA Negeri 1 Kepahiang - Suharmi Suharmi; Raissa Citra Nabila (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aims to determine the effect of the use of social media for students in class XI IPS on economics subjects at SMA Negeri 1 Kepahiang. Knowing the learning outcomes of Class XI Social Studies students in Economics at SMA Negeri 1 Kepahiang. Knowing how much influence the use of social media has on the learning outcomes of Class XI Social Studies students in Economics at SMA Negeri 1 Kepahiang. This type of research is quantitative research using statistical analysis of simple linear regression test. The population of this study were all students of class XI IPS at SMA Negeri 1 Kepahiang as many as 181 people. The sampling technique used was simple random sampling. The sample taken amounted to 52 students. Data collection techniques using observation, questionnaires and documentation. The results showed that the use of social media by students of class XI IPS at SMA Negeri 1 Kepahiang was overall in the interval range of 68-83 so it was categorized as good, with an average value of 69.2%, student learning outcomes of class XI IPS in Economics in SMA Negeri 1 Kepahiang as a whole is in the interval range of 71-80 so it is categorized as Good, with an average value of 76%, and there is an influence of social media on the learning outcomes of class XI IPS students in Economics at SMA Negeri 1 Kepahiang, this is obtained from the results of a simple linear regression value Y = 34.5 + 0.60 X with a calculated f value greater than f table (19.41 > 4.03) and the level of influence is 28%.